A tunable single-photon multi-channel quantum router in a hybrid BEC-optomechanical system. (11th April 2019) - Liu, Liwei; Zhang, Guoheng; An, Xiujia; Hai, Lian; Jiao, Haiyan; Wang, Peiyu
Abstract: A novel technique for generating a single-photon multi-channel quantum router in a hybrid BEC-optomechanical system is proposed. This system consists of a cigar-shaped Bose–Einstein condensate that is trapped inside a high-finesse Fabry–Pérot cavity with a moving end-mirror. Analytical solutions are given for the spectrum of the reflectance and transmittance of the output field. When the cavity is driven by a coupling laser and probe laser, we can produce a switch for the appropriate of the normalized frequency and the effective coupling strength. Furthermore, the effective coupling strength of the optical field with the condensate mode, the effective coupling strength of the optical field with the mirror, cavity decay and decay rates for the moving mirror are used to control the number of the single-photon quantum router. Finally, we also demonstrate the vacuum, and thermal noise can be insignificant for the single-photon router. We give a certain set of experimental parameters for observing these phenomena in the laboratory. The technique presented may have potential applications in quantum engineering and quantum information networks.